Hernia Through Winslow Foramen in Cipto Mangunkusumo General Hospital, Jakarta: A Case Report - Ristiyanto, Eko; Wibowo, Taufik A; Syaiful, Ridho A; Philippi, Benny; Lalisang, Toar J.M. (The New Ropanasuri Journal of Surgery, 2020)
Introduction. Hernias through Winslow foramen are extremely rare, occurred for 0.1% of all abdominal hernias and found during laparotomy due to strangulated bowel obstruction. This study aims to describe hernia of Winslow foramen and its management. Method. Data were retrospectively collected based on medical records. Clinical manifestations, laboratory data, supporting radiographic examinations, treatment, postoperative care, and outcomes were collected. Case summary. We report the first case of Winslow foramen hernia at Cipto Mangunkusumo General Hospital, Jakarta. A man 54 years in 2019. Ileus was the main clinical symptoms and presented epigastric pain, nausea and vomiting. Plain abdominal x-ray confirmed small bowel obstruction but the etiology was unclear. Emergency laparotomy was performed and a herniated loop of ileum was found entering the lesser sac through the Winslow foramen. The loop of ileum was reduced and viable, omental patch was put on Winslow foramen as plasty procedure. Conclusion. Symptoms, clinical examination is non-specific and laboratory findings are rarely helpful. Retrograde analysis on the plain abdominal x-ray should be considered as abdominal internal hernia through Winslow foramen. The surgical management of hernia through Winslow foramen based on surgeon preference and the viability of the herniated intra-abdominal contents.